Control of rust mite in citrus - Oliveira, Carlos Amadeu L. de (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of the present work was to evaluate the miticidal action of MK 936 (avermectin) SL and EC formulations applied isolately or in mixture with mineral oil, in the control of the rust mite in a citrus orchard, and their effects on the predator mite population. Two trials were conducted in citrus of “Pêra”, variety, at “Faculdade de Ciéncias Agrárias e Veterinárias de Jaboticabal”, and it was concluded that: a) MK 936 SL and EC were equallyefficientin the control of rust mite Phyllocoptruta oleivora; b) - the mixture with mineral oil showed better efficiency and was active for a longer time; c) - MK 936 was similar to chlorobenzilate in efficiency ;d) - dicofol was very efficient in the control of rust mite, but caused a remarkable resurgence of mite.